1984
DOI: 10.1111/j.1600-0404.1984.tb07815.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis: periphlebitis retinalis et cerebro-spinalis A correlation between periphlebitis retinalis and abnormal technetium brain scintigraphy

Abstract: Periphlebitis retinae (PR) in multiple sclerosis (MS) is seen as transitory infiltrations around veins in the otherwise normal retina. Cellular infiltrations have been found around veins in the central nervous system (CNS), where it has been suggested that they are the first event in plaque formation. Technetium brain scans are usually normal in MS patients, but transitory abnormal scans of the cerebrum have been found in MS patients during acute attack or exacerbation. In order to test the hypothesis that act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 12 publications
1
4
0
1
Order By: Relevance
“…These data, therefore, are consistent with the hypothe sis that the venular changes may be considered as a marker of disease activity, as also suggested by the studies of Engell et al [16,17], particularly in the early stages, given the good correlation found between PR and short duration of the disease. The different methodologies of case collection in the various studies which lead to a dif ferent probability of including patients with active disease may further explain the wide range of reported PR preva lence in MS [20],…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These data, therefore, are consistent with the hypothe sis that the venular changes may be considered as a marker of disease activity, as also suggested by the studies of Engell et al [16,17], particularly in the early stages, given the good correlation found between PR and short duration of the disease. The different methodologies of case collection in the various studies which lead to a dif ferent probability of including patients with active disease may further explain the wide range of reported PR preva lence in MS [20],…”
Section: Discussionsupporting
confidence: 79%
“…Adams et al [12] suggested cerebral periphlebitis to be a precursor of plaque formations in surrounding tissues. A transitory breakdown of the bloodbrain barrier has been well documented at the time of dis ease activity by Tc-scintigraphy [13], CT scan [14], and more recently by MRI with gadolinium [15], Engell et al [16] found similar barrier damage in MS patients with PR, and analogous functional changes of the blood-retinal barrier during RP attacks, measured by vitreous fluorophotometry [ 17], Considering these simultaneous fea tures in the retina and the brain, and the similarity of their pathological aspects, it is reasonable to suppose a com mon etiopathogenesis for PR and CNS MS lesions, and to speculate that both ocular and cerebrum changes repre sent a primary phlebitic process that in the brain leads to demyelination, and in the retina, which is embryologically an extension of the CNS. stops at an early stage due to a lack of myelin in this site.…”
Section: Discussionmentioning
confidence: 99%
“…7 Active retinal periphlebitis tends to occur simultaneously with blood-brain-barrier disruption in MS, 8 and may be a risk factor for relapses and gadolinium-enhancing lesions. 9 Intermediate uveitis, particularly parsplanitis, also occurs in up to 16% of MS patients.…”
Section: Introductionmentioning
confidence: 99%
“…These findings raise the possibility that the potential mechanism underlying the proposed occurrence of primary retinal pathology affecting the INL in MS may be inflammatory, 1, 2 such as related to retinal periphlebitis. Retinal periphlebitis is known to occur in up to 20% of MS patients, 10, 40 and it has previously been shown that active retinal periphlebitis and disruption of the blood-brain-barrier tend to occur simultaneously in MS. 41 Moreover, the presence of retinal periphlebitis in MS patients has been shown to be a risk factor for the subsequent development of relapses and gadolinium-enhancing lesions. 28 ONL thickness also appears to have relationships with brain-substructure volumes.…”
Section: Discussionmentioning
confidence: 99%